MWCNT/Ruthenium hydroxide aerogel supercapacitor production and investigation of electrochemical performances - Satiye Korkmaz; İshak Afşin Kariper; Ceren Karaman; Onur Karaman (Scientific Reports, 2022)
Abstract In this study, the material obtained from the sonication of the double-walled carbon nanotube and ruthenium chloride was produced as an aerogel. Then, symmetrical supercapacitor devices were made using them, and their electrochemical properties were investigated. XRD and FTIR were used in the structural analysis of the aerogel, STEM in surface images, and elemental analyses in EDX. Electrochemical analysis was performed by galvanostat/potentiostat. From the cyclic voltammetry analysis, the highest specific capacitance for MWCNT/Ruthenium hydroxide aerogels was achieved as 423 F/g at 5 mV/s. On the other hand, the corresponding values calculated from the charge–discharge curves were found to be 420.3 F/g and 319.9 F/g at the current densities of 0.5 A/g and 10.0 A/g, respectively. The capacitance retention of as-synthesized aerogel was 96.38% at the end of the 5000 consecutive consecutive cyclic voltammetry cycles.